Video-Assisted Problem Based Learning Model to Improve Students’ Critical Thinking Skills in Environmental Pollution - Maulina, Dina; Priadi, Median Agus; Viyanti, Viyanti; Wijaya, Agung Putra; Ibirilia, Elvira Sesie; Nurhadian, Yardan Permata (Jurnal Pendidikan MIPA, 2024)
This study investigated the effect of using a video-assisted problem-based learning model on class VII students' critical thinking abilities on environmental pollution material. This research was conducted using quasi-experimental research design with a non-equivalent control group. The research data were in the form of qualitative data (critical thinking skills) and quantitative (student responses to learning using the video-assisted PBL model). Data analysis used the T-test (p<0.05). The results showed that there was an influence of using the video-assisted PBL model on students' critical thinking skills on environmental pollution material (p<0.05). The indicator for building basic skills obtained the highest average N-gain, namely 0.82 in the very good category. Meanwhile, the results of the student response questionnaire regarding the use of the video-assisted PBL model showed positive student responses with an average score of 89.67% in the very good category.         Keywords: critical thinking skills, PBL, environmental pollution and video. DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp486-495